Cancer History and Systemic Anti-Cancer Therapy Independently Predict COVID-19 Mortality: A UK Tertiary Hospital Experience - Sng, Christopher C. T.; Wong, Yien Ning Sophia; Wu, Anjui; Ottaviani, Diego; Chopra, Neha; Galazi, Myria; Benafif, Sarah; Soosaipillai, Gehan; Roylance, Rebecca; Lee, Alvin J. X.; Shaw, Heather (Frontiers in Oncology, 2020)
Background The COVID-19 pandemic remains a pressing concern to patients with cancer as countries enter the second peak of the pandemic and beyond. It remains unclear whether cancer and its treatment contribute an independent risk for mortality in COVID-19. Methods We included patients at a London tertiary hospital with laboratory confirmed SARS-CoV-2 infection. All patients with a history of solid cancer were included. Age- and sex-matched patients without cancer were randomly selected. Patients with hematological malignancies were excluded. Results We identified 94 patients with cancer, matched to 226 patients without cancer. After adjusting for age, ethnicity, and co-morbidities, patients with cancer had increased mortality following COVID-19 (HR 1.57, 95% CI:1.04–2.4, p = 0.03). Increasing age (HR 1.49 every 10 years, 95% CI:1.25–1.8, p < 0.001), South Asian ethnicity (HR 2.92, 95% CI:1.73–4.9, p < 0.001), and cerebrovascular disease (HR 1.93, 95% CI:1.18–3.2, p = 0.008) also predicted mortality. Within the cancer cohort, systemic anti-cancer therapy (SACT) within 60 days of COVID-19 diagnosis was an independent risk factor for mortality (HR 2.30, 95% CI: 1.16–4.6, p = 0.02). Conclusions Along with known risk factors, cancer and SACT confer an independent risk for mortality following COVID-19. Further studies are needed to understand the socio-economic influences and pathophysiology of these associations.